2021
DOI: 10.3390/pr9030445
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Coating Effect on the Characteristics of Liposomes: A Focus on Bioactive Compounds and Essential Oils: A Review

Abstract: In recent years, liposomes have gained increasing attention for their potential applications as drug delivery systems in the pharmaceutic, cosmetic and food industries. However, they have a tendency to aggregate and are sensitive to degradation caused by several factors, which may limit their effectiveness. A promising approach to improve liposomal stability is to modify liposomal surfaces by forming polymeric layers. Among natural polymers, chitosan has received great interest due to its biocompatibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 111 publications
3
36
0
Order By: Relevance
“…Argan oil enriched liposomes have a softening and relaxing effect on the skin, thus facilitating the payload accumulation and its passage into and through it [29]. Moreover, essential oils such as Thymus capitatus essential oil [30], clove essential oil [31], Zanthoxylum tingoassuiba essential oil [32], pompia essential oil [33] and others [34], have been loaded in phospholipid vesicles, aiming at improving the oil biological efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Argan oil enriched liposomes have a softening and relaxing effect on the skin, thus facilitating the payload accumulation and its passage into and through it [29]. Moreover, essential oils such as Thymus capitatus essential oil [30], clove essential oil [31], Zanthoxylum tingoassuiba essential oil [32], pompia essential oil [33] and others [34], have been loaded in phospholipid vesicles, aiming at improving the oil biological efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the lipophilic nature of EOs components, their high volatility and chemical instability, the encapsulation in nanoformulated delivery systems could be an approach to overcome such limitations and boost the antidermatophytic activity of EOs [15,22,82]. The additional data regarding their skin and nail permeation, elucidation of their mechanism of activity, and whether in vitro results translate into similar outcomes in in vivo models, are in high demand.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that chitosan coating improves the stability of soft lipid vesicles by forming a wall that prevents swelling and release of the encapsulated drug (e.g., natural compounds, anti-inflammatory drugs, antimicrobials, hormonal medication, cardiovascular medication) [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%